The effect of mere presence of smartphone on cognitive functions: A four-level meta-analysis - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2024)
As smartphones have become portable and immersive devices that afford social, informational, and recreational conveniences unbounded by physical restrictions, most daily activities have become closely intertwined with the presence of smartphones. This constant presence of smartphones in daily activities, however, may be concerning as some studies have suggested that smartphones—even their mere presence—can be distracting and can impair cognitive outcomes. However, such findings have not been consistently observed. To reconcile mixed findings, the current meta-analysis synthesized 166 effect sizes drawn from 53 samples and 33 studies including 4,368 participants on the effect of mere presence of smartphone on cognitive functions. It was found that the mere presence of smartphone had no significant effect on cognitive outcomes (d = −0.02, SE = 0.02, 95% CI [−0.06, 0.01], p = .246). Further, the effect of mere presence of smartphone was not moderated by demographics, trait smartphone dependency, or various methods for manipulating smartphone presence and assessing cognitive outcomes. These findings indicate that there is little reason at present to think that complete isolation from smartphones in a work environment would improve productivity and performance.